Molecular mechanisms controlling phosphate-induced downregulation of the yeast Pho84 phosphate transporter - Lundh, Fredrik; Mouillon, Jean-Marie; Samyn, Dieter; Stadler, Kent; Popova, Yulia; Lagerstedt, Jens O; Thevelein, Johan M; Persson, Bengt L (Biochemistry (Easton), 2009)
In Saccharomyces cerevisiae, phosphate uptake is mainly dependent on the proton-coupled Pho84 permease under phosphate-limited growth conditions. Phosphate addition causes Pho84-mediated activation of the protein kinase A (PKA) pathway as well as rapid internalization and vacuolar breakdown of Pho84. We show that Pho84 undergoes phosphate-induced phosphorylation and subsequent ubiquitination on amino acids located in the large middle intracellular loop prior to endocytosis. The attachment of ubiquitin is dependent on the ubiquitin conjugating enzymes Ubc2 and Ubc4. In addition, we show that the Pho84 endocytotic process is delayed in strains with reduced PKA activity. Our results suggest that Pho84-mediated activation of the PKA pathway is responsible for its own downregulation by phosphorylation, ubiquination, internalization, and vacuolar breakdown.